Antioxidant Properties and Characterization of Heterotrigona itama Honey from Various Botanical Origins according to Their Polyphenol Compounds - Sharina Shamsudin; Jinap Selamat; Mukramah Abdul Shomad; Muhamad Faris Ab Aziz; Md. Jahurul Haque Akanda (Journal of Food Quality)
Stingless bee honey is a good source of antioxidants, which is attributed to the phenolic compounds. The type and concentration of phenolic compounds in honey can be affected by botanical origin. Therefore, in this study, Heterotrigona itama honey from three botanical origins (gelam, acacia, and starfruit) was evaluated for its antioxidant activity and profile of phenolic compounds. Apis mellifera honey was used as a comparison. Antioxidant activity and profile of phenolic compounds in honey were determined using spectrophotometric and chromatographic methods, respectively. The total phenolic content (TPC), total flavonoids content (TFC), free radical scavenging activity (IC50), and ferric reducing antioxidant power (FRAP) of H. itama were ranged between 52.64 and 74.72 mg GAE/100 g honey, 10.70–25.71 mg QE/100 g honey, 11.27–24.09 mg/mL, and 77.88–164.88 µmol FeSO4.7H2O/100 g honey, respectively. The findings showed that the antioxidant activity and phenolic and flavonoid contents in H. itama honey were significantly higher than Apis honey. Benzoic acid and taxifolin were found as the predominant phenolic acid and flavonoid in all samples. However, chrysin was significantly highest in Apis honey than stingless bee honey. This result suggested that chrysin can be used as a chemical marker to distinguish Apis honey from stingless bee honey. Gallic acid and ellagic acid were found as the chemical marker for gelam honey, salicylic acid, benzoic acid, and 4-hydroxybenzoic acid for starfruit honey while ferulic acid for acacia honey.